XVI American Literature: The Twentieth Century. Issue 1 (12th September 2021) - Gifford, James; Clawson, James M; Foltz, Mary; Kidder, Orion Ussner; Peppard, Anna; Parker, Lindsay
Abstract: This chapter has eight sections: 1. Poetry; 2. Fiction 1900–1945; 3. Fiction since 1945; 4. Drama; 5. Comics; 6. African American Writing; 7. Native Writing; 8. Latino/a, Asian American, and General Ethnic Writing. Section 1 is by James Gifford; section 2 is by James M. Clawson; section 3 is by Mary Foltz; section 4 will resume next year; section 5(a) is by Anna Peppard; section 5(b) is by Orion Ussner Kidder; section 6 is by Adam Rudder; section 7 is by James Gifford and Lindsay Parker; section 8 will resume next year.